2023
DOI: 10.1038/s41598-023-42890-9
|View full text |Cite
|
Sign up to set email alerts
|

Laterality influence on gene expression of DNA damage repair in colorectal cancer

Juliano Oliveira-Silveira,
Eduardo Filippi-Chiela,
Jenifer Saffi

Abstract: Colorectal carcinoma (CRC) is the third most common malignancy worldwide, and second in number of deaths in the world. The molecular pathogenesis of CRC is heterogeneous and can affect several genes. Moreover, genomic instability is recognized as an important part of CRC carcinogenesis and is tightly connected to DNA damage response. DNA damage repair (DDR) pathways are intrinsically associated with cancer development and establishment. Traditionally, CRC is considered as one coherent disease, however, new evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This study and others have shown that KRAS mutation was more frequent in right sided CRC [37, 54, 55]. The predilection of KRAS mutations for the right side of the colon may be influenced by the fact that the right and left side of the colon have different biology and histopathology in their respective embryological origins [37, 56, 57]. Right-sided CRC often has flat histopathology and a DNA mismatch repair pathway deficiency [58].…”
Section: Discussionmentioning
confidence: 76%
“…This study and others have shown that KRAS mutation was more frequent in right sided CRC [37, 54, 55]. The predilection of KRAS mutations for the right side of the colon may be influenced by the fact that the right and left side of the colon have different biology and histopathology in their respective embryological origins [37, 56, 57]. Right-sided CRC often has flat histopathology and a DNA mismatch repair pathway deficiency [58].…”
Section: Discussionmentioning
confidence: 76%
“…This study and others have shown that KRAS mutation was more frequent in right-sided CRC [ 48 , 72 , 73 ]. The predilection of KRAS mutations for the right side of the colon may be influenced by the fact that the right and left sides of the colon have different biology and histopathology in their respective embryological origins [ 48 , 74 , 75 ]. Right-sided CRC often has flat histopathology and a DNA MMR pathway deficiency [ 76 ].…”
Section: Discussionmentioning
confidence: 99%